The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0232645
|View full text |Cite
|
Sign up to set email alerts
|

β-adrenergic receptor signaling evokes the PKA-ASK axis in mature brown adipocytes

Abstract: Boosting energy expenditure by harnessing the activity of brown adipocytes is a promising strategy for combatting the global epidemic of obesity. Many studies have revealed that the β 3 -adrenergic receptor agonist is a potent activator of brown adipocytes, even in humans, and PKA and p38 MAPK have been demonstrated for regulating the transcription of a wide range of critical genes such as Ucp1 . We previously revealed that the PKA-ASK1-p38 axis is activated in imm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Alternatively, our results may point out the existence of latent beneficial aspect of ASK1 upregulation through tuning the NOD-RIPK2 pathway under obesity. As a potential relevant finding to this assumption, we previously demonstrated that global Ask1 knockout mice showed impaired glucose clearance compared to wild-type mice under high-fat diet treatment, and the phenotype was more robust in severely obese animals 20 . Unexpectedly, however, adipocyte-specific Ask1 knockout mice exhibited comparable glucose clearance with wild-type 20 , which denies the potential influence of ASK1 on blood glucose level under obesity through downregulating the pro-inflammatory NOD-RIPK2 pathway in adipocytes.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Alternatively, our results may point out the existence of latent beneficial aspect of ASK1 upregulation through tuning the NOD-RIPK2 pathway under obesity. As a potential relevant finding to this assumption, we previously demonstrated that global Ask1 knockout mice showed impaired glucose clearance compared to wild-type mice under high-fat diet treatment, and the phenotype was more robust in severely obese animals 20 . Unexpectedly, however, adipocyte-specific Ask1 knockout mice exhibited comparable glucose clearance with wild-type 20 , which denies the potential influence of ASK1 on blood glucose level under obesity through downregulating the pro-inflammatory NOD-RIPK2 pathway in adipocytes.…”
Section: Discussionmentioning
confidence: 94%
“…As a potential relevant finding to this assumption, we previously demonstrated that global Ask1 knockout mice showed impaired glucose clearance compared to wild-type mice under high-fat diet treatment, and the phenotype was more robust in severely obese animals 20 . Unexpectedly, however, adipocyte-specific Ask1 knockout mice exhibited comparable glucose clearance with wild-type 20 , which denies the potential influence of ASK1 on blood glucose level under obesity through downregulating the pro-inflammatory NOD-RIPK2 pathway in adipocytes. Nevertheless, considering the confounding example of body weight in the phenotype of Ask1 knockout mice and complexity of obesity-induced inflammatory response in vivo, we should keep in mind that negative regulation of the NOD-RIPK2 pathway by ASK1 in brown adipocytes may contribute to unidentified whole-body phenotype in some obesity-associated situation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation